Cytotoxic Prenylated Xanthones from the Pericarps of Garcinia mangostana - Zeng Xu (Molecules, 2014)
Bioassay-guided fractionation of an ethanol extract of the pericarps of Garcinia mangostana led to the isolation of two new prenylated xanthones, named 1,3,7-trihydroxy-2-(3-methyl-2-butenyl)-8-(3-hydroxy-3-methylbutyl)-xanthone (1) and 1,3,8-trihydroxy-2-(3-methyl-2-butenyl)-4-(3-hydroxy-3-methylbutanoyl)-xanthone (2), together with the five known compounds garcinones C (3) and D (4), gartanin (5), xanthone I (6), and γ-mangostin (7). Their structures were elucidated primarily based on MS and NMR data. Compounds 1–7 showed significant cytotoxic activities against various human cancer cell lines.